Interethnic relations between Belarusians and Poles under the conditions of the new state identity development in 1921–1939 - N.A. Markelov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper is focused on the specifics of interethnic interaction of Belarusian and Polish communities in Western Belarus during 1921–1939. The subject of the analysis is the specific character of the state identity development under the conditions of the frontier region and its influence on the coresidence of the two main ethnic groups representing different cultural\civilizational areas (“the Russian World” – Belarusians and “the West” – Poles). The sources of the paper are the publications of the National Archive of the Republic of Belarus, as well as the works of modern Belarusian, Russian, and Polish scholars. The theoretical basis of the research is formed by the works of Russian academic authors, who developed the theory of frontier applicable to the Eastern European cases. The contradictions between Polish jurisdiction that neglected the basic national rights of minorities (the paper demonstrates its manifestations in education, religious life, and policy pursued by the authorities against any nation-identifying non-Polish cultural activities) and natural pro-Russian orientation of the Belarusian population (especially of the Orthodoxy adherents) led not only to the ethnic conflict, but to the appearance of a stronger regional identity, which was not subjected to the direct persecution. The above-described processes resulted in the failure of II Polish Republic's forced polonization programs. The importance of the phenomenon of substitution of national identity by a regional one was proved by latter historical events. The omission of this fact in both USSR's and after-war Poland's government strategies concerning the region complicated the integration of Western Belarus into the Soviet state (in the BSSR), extended the period of instability after the World War II (in the whole region), consolidated the profound and hidden unfriendliness between the neighboring Slavic nations – Poles and Belarusian (in the part of the region controlled by Poland).